Mortality in Dermatology: A Closer Look - Prachi Bhandare; Annam Navya; Rakhi Ghodge; Pankaj Shukla; Taruna Gupta (Indian Journal of Medical Specialities)
Introduction: Contrary to the general perception that the field of dermatology rarely encounters managing critical patients and dealing with mortality, severe and extensive dermatological conditions can be lethal in the absence of timely intervention. Aims and Objectives: The aim was to study in detail regarding the deaths and the various factors associated with it in patients admitted with dermatological conditions in a tertiary care center over a period of 10 years. Materials and Methods: It was a retrospective, record-based, observational study over a period of 10 years (2011–2021) in a tertiary care hospital consisting of 49 cases. After obtaining institutional ethical clearance, the information was obtained from medical records section. The relevant details of patients were entered in a specially formulated proforma. Results: A total of 3491 patients were admitted to the Department of Dermatology, Goa Medical College, during the study period of 10 years from January 2011 to August 2021. Among these, 49 patients succumbed to their skin condition, with an overall mortality percentage of 1.4%. Drug reactions were the most commonly encountered diagnosis in 17 patients (34.69%) which was closely followed by vesiculobullous disorders with 14 (28.57%) cases and infections in 10 (20.40%) cases. Conclusion: Drug reactions, vesiculobullous disease, and infections were the main causes of mortality in our series of patients. Extensive skin and mucosal involvement, multisystem involvement, declining age, delay in treatment received, and onset of sepsis were some of the major factors contributing to mortality. In our study, a high proportion of 46.93% of the patients were above the age of 60 years, out of which 56.52% had vesiculobullous disease. Hence, a special focus on geriatric dermatology deserves attention, especially in tertiary care centers.